2017
DOI: 10.4028/www.scientific.net/kem.733.47
|View full text |Cite
|
Sign up to set email alerts
|

Neutronic Analysis of Thorium Nitride (Th, U233)N Fuel for 500MWth Gas Cooled Fast Reactor (GFR) Long Life without Refueling

Abstract: Neutronic analysis of Thorium Nitride (Th, U233)N fuel of 500MWth Gas Cooled Fast Reactor (GFR) has been done. In this study the neutronic analysis use SRAC2006 code both PIJ and CITATION calculation. The data libraries use JENDL 4.0. First calculation is survey parameter with U-233 enrichment variation. From the homogeneous core configuration calculation, when the enrichment of U-233 is 8.2%, the maximum k-eff value is 1,00819 with excess reactivity value 0,812%. The average power density is 63 Watt/cc and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Previous research has been conducted on neutronic analysis for GFR with thorium nitride fuel using SRAC. Some of the research on GFR using thorium nitride fuel are [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has been conducted on neutronic analysis for GFR with thorium nitride fuel using SRAC. Some of the research on GFR using thorium nitride fuel are [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The configuration of the heterogeneous core has a lower neutron flux distribution than the homogeneous core. The resulting fission reaction is more even, thus minimizing the peaking power in the reactor core [11]. However, further studies need to be made for the use of the heterogeneous core with certain variations (more than 2 fuel variations) to produce a more even distribution of neutron flux and a more stable level of criticality (k eff ≈ 1).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on the addition of minor actinides in the fuel in the Gas-Cooled Fast Reactor (GFR) has been carried out [14][15][16]. The study found that the addition of minor actinides could reduce the k-eff value.…”
Section: Introductionmentioning
confidence: 99%